Effects of temperature and salinity on inducing spawning in the eastern oyster (Crassostrea virginica) under laboratory conditions - Magaña Carrasco, Antonio; Brito Manzano, Nancy Patricia; Gómez Vázquez, Armando; Cruz-Hernández, Aldenamar (Ecosistemas y Recursos Agropecuarios, 2018)
The effectiveness of two stimuli (thermal and salinity shock) in inducing spawning in the eastern oyster Crassostrea virginica was tested under laboratory conditions. Organisms were obtained in Machona Lagoon, located in Sánchez Magallanes, Tabasco. Temperatures used were 10, 15, 20, 25 and 30 ◦C and the salinities were 10, 15, 20, 25 and 30 psu. The objective of this work was to determine the effects of salinity and thermal shock on spawning of C. virginica oyster. The best spawning results were obtained by using salinity shock, which induced spawning in 55% of the oysters tested, with the number of males that spawned being signi cantly higher than that of the females. Thermal shock was less e ective with only 34% of organisms spawning and, unlike the salinity results, the number of females was higher than that of males. Temperatures of 30 ◦C or greater had a negative e ect on spawning and was similar at a salinity of 30 psu. The optimum time for spawning was between 11 and 15 min of exposure to salinity shock, whilst for thermal shock it was between 16 and 20 min.